Ascending Colon Cancer with Pathologically Confirmed Tumor Thrombosis of Superior Mesenteric Vein: A Case Report - Sung Eun Kim; Sang Jin Lee; Jun Young Cha; Sang Won Yi; Tae Sun Kim; Il Leon Cho; Jae Young Kwak; Kwang Hoon Oh (Korean Society of Gastrointestinal Endoscopy, 2019)
Colon cancer is very rarely accompanied by tumor thrombosis of the superior mesenteric vein (SMV). A 46-year-old patient had been diagnosed with SMV tumor thrombosis related to colon cancer without hepatic metastasis and underwent right hemicolectomy with SMV tumor thrombectomy. Tumor thrombosis was pathologically confirmed as metastatic colon cancer. There has been no recurrence for 12 months with 12 cycles of adjuvant-chemotherapy.